2021
DOI: 10.3390/pharmaceutics13091442
|View full text |Cite
|
Sign up to set email alerts
|

Safety Testing of an Antisense Oligonucleotide Intended for Pediatric Indications in the Juvenile Göttingen Minipig, including an Evaluation of the Ontogeny of Key Nucleases

Abstract: The adult Göttingen Minipig is an acknowledged model for safety assessment of antisense oligonucleotide (ASO) drugs developed for adult indications. To assess whether the juvenile Göttingen Minipig is also a suitable nonclinical model for pediatric safety assessment of ASOs, we performed an 8-week repeat-dose toxicity study in different age groups of minipigs ranging from 1 to 50 days of age. The animals received a weekly dose of a phosphorothioated locked-nucleic-acid-based ASO that was assessed previously fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 139 publications
2
12
0
Order By: Relevance
“…On the other hand, a previous study in adult Göttingen minipigs treated with various LNA-based PS ASOs did not show a fall in platelet count following four weeks of treatment [29]. This is also in line with the repeat-dose toxicity study conducted in juvenile Göttingen minipigs treated with RTR5001, an LNA-modified PS ASO, in which no fall in platelet count was seen after a drug exposure of up to eight weeks [30]. However, the effect of different types of ASOs on Göttingen minipig platelets, including their potential activation mechanism, has not yet been characterized.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…On the other hand, a previous study in adult Göttingen minipigs treated with various LNA-based PS ASOs did not show a fall in platelet count following four weeks of treatment [29]. This is also in line with the repeat-dose toxicity study conducted in juvenile Göttingen minipigs treated with RTR5001, an LNA-modified PS ASO, in which no fall in platelet count was seen after a drug exposure of up to eight weeks [30]. However, the effect of different types of ASOs on Göttingen minipig platelets, including their potential activation mechanism, has not yet been characterized.…”
Section: Introductionsupporting
confidence: 85%
“…Seven tool ASOs were assessed to investigate their effects on adult Göttingen minipig platelets (Table 1). Accordingly, ODN2395 (PS oligonucleotide known to cause platelet activation and aggregation) and its unmodified isosequential variant [22,27,28]; ISIS104838 (2 MOE/PS/2 MOE gapmer that causes thrombocytopenia in NHPs and humans) [18,19,21,27] and its all-PS variant; and RTR5001 (LNA/PS/LNA gapmer that does not cause platelet count alteration) [29,30,37,38] together with its all-PS and unmodified variant were included and described in Table 1. In particular, RTR5001 targets the human PCSK9 transcript (NCBI reference sequence: NM_174936.3) and has a single end-standing mismatch to the minipig sequence, which did not ablate its pharmacologic effects in the minipigs [29,30].…”
Section: Antisense Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have shown that inotersen causes 2%‐% of severe cases of thrombocytopenia 79‐81 . Autoimmune dysregulation and antiplatelet IgG antibody production in hATTR patients has been suggested as a potential mechanism for inotersen‐induced thrombocytopenia 82,83 . The study and clinical trials presented contradictory results and there were fewer pharmacovigilance studies and case reports on inotersen.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurement of OT concentrations in brain regions such as the cerebral cortex and hippocampus has been performed to assess brain drug distribution (Jafar‐Nejad et al., 2021; Mazur et al., 2019). Hybridization enzyme‐linked immunosorbent assay (HELISA) is widely used for pharmacokinetic evaluation (Mazur et al., 2019; Shi et al., 2021; Valenzuela et al., 2021). HELISA is a highly sensitive method and does not require expensive equipment or specific extraction techniques, despite concerns about cross‐reactivity with metabolites (Chan et al., 2010; Yu et al., 2002).…”
Section: It and Icv Administration As The Current Gold Standard Approachmentioning
confidence: 99%